Gemini IFU, VLA, and HST observations of the OH Megamaser Galaxy IRAS17526 + 3253★. Issue 3 (18th January 2019) - Sales, Dinalva A; Robinson, A; Riffel, R A; Storchi-Bergmann, T; Gallimore, J F; Kharb, P; Baum, S; O'Dea, C; Hekatelyne, C; Ferrari, F
Abstract: We present a multiwavelength study of the OH megamaser galaxy IRAS17526 + 3253, based on new Gemini multi-object spectrograph integral field unit (GMOS/IFU) observations, Hubble Space Telescope F814W, and H α + [N ii ] images, and archival 2MASS and 1.49 GHz VLA data. The Hubble Space Telescope ( HST ) images clearly reveal a mid-to-advanced stage major merger whose northwestern and southeastern nuclei have a projected separation of ∼8.5 kpc. Our HST /H α + [N ii ] image shows regions of ongoing star formation across the envelope on ∼10 kpc scales, which are aligned with radio features, supporting the interpretation that the radio emission originates from star-forming regions. The measured H α luminosities imply that the unobscured star formation rate (SFR) is ∼10–30 M⊙ yr −1 . The GMOS/IFU data reveal two structures in northwestern separated by 850 pc and by a discontinuity in the velocity field of ∼ 200 km s −1 . We associate the blueshifted and redshifted components with, respectively, the distorted disc of northwestern and tidal debris, possibly a tail originating in southeastern. Star formation is the main ionization source in both components, which have SFRs of ∼2.6–7.9 M⊙ yr −1 and ∼1.5–4.5 M⊙ yr −1, respectively. Fainter line emission bordering these main components is consistent with shock ionization at a velocity ∼200 km s −1 and may be the result of an interaction between the tidal tail and the northwestern galaxy's disc. IRAS17526 + 3253 is one of only a few systems known to host both luminous OH and H2 O masers. The velocities of the OH and H2 O maser lines suggest that they are associated with the northwestern and southeastern galaxies, respectively (Martin et al.; Wagner).